Biodistribution of the Informal Group Basommatophora in the Philippines - Young, Patrick Noel Y.; Fontanilla, Ian Kendrich C. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 26 No 1 (2014))
Basommatophora is an informal group within the molluscan subclass Pulmonata comprising of air-breathing freshwater snails that are typically characterized by eyespots located at the base of two noncontractile tentacles and two external genital orifices. They also have varied shell structures and habitats, not only within the group but also within families. Families of the Basommatophora are highly ubiquitous and may play a role in the life cycles of various parasites of humans and animals. Basommatophora has a worldwide geographical distribution across freshwater, terrestrial and marine habitats. However, little is known on their distribution in the Philippines. This report focuses on describing the biogeographical distribution of the basommatophorans in the Philippines through data gathered from museum collections, foreign databases accessed online, and identification of species found in various literatures. A qualitative description of the distribution of each Basommatophora family in the Philippines is given by distribution maps, indicating locations where specimens were collected and/or identified. A total of 336 counts of basommatophorans from 22 genera were encountered from available literature, museums and public databases. The majority of the occurrences are from the genera Siphonaria. The data and maps generated describe most of the distribution to be in Luzon, with Visayas and Mindanao having close counts with each other. The Philippines has the third most occurrences and genera of basommatophorans of all tropical countries in the world. However, the true diversity of the group could be higher if a more systematic sampling of the archipelago is conducted. Keywords: Basommatophora, Philippines, biogeographical distribution